Banks' Risk and The Impact of Audit Quality on Income Smoothing - Konstantinos Vasilakopoulos; Christos Tzovas; Apostolos Ballas (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research question -This paper investigates the impact that specific audit quality dimensions have upon European Union Banks' income smoothing behavior. Motivation - Although previous studies have investigated the characteristics of audit quality, little is known about the audit quality in the banking sector. Excessive risk taking and business complexity may further impair auditors' work and an audit's outcome may be conditioned upon banks' risk. Idea - We examine whether auditors' independence influences bank managers' decision to smooth income and whether this attribute depends on bank risk and systemic importance. We investigate the association between auditors' industry specialization and auditors' tenure with the level of Loan Loss Provisions Data - We use a sample of 133 banks from 26 European Union countries for the period 2006-2013. Tools - Similar to previous research, we use ordinary least squares analysis to test the results. Findings - Empirical findings provide evidence that the auditors' industry expertise limits management's discretion of high-risk banks to a greater extent relative to low risk banks. In contrast, our results imply that banks that retain the same auditor for a consecutive fiscal year are more likely to engage in income smoothing through LLPs. Furthermore, our study examines whether audit quality dimensions have different outcomes on income smoothing decisions between globally systemically important banks (GSIBs) and the rest of banks. Our results provide evidence that the impact of industry specialization and auditor tenure on EU banks accounting policy decisions differs between GSIBs and non-GSIBs. Contribution - Our analysis contributes in the existing body of research by focusing on the impact of audit quality on managements' accounting discretion and the influence of banks' special attributes on the audit process.
Keywords: G21; G14; M41; M42; 650; banks; provisions; income smoothing; auditor expertise; auditor tenure